Psychosocial Resources of People with Low Vision - Beata Szabała (Maria Curie-Skłodowska University, Lublin, Poland, 2022)
Introduction: The development of coping strategies as well as the support tailored to the needs of people with low vision allow for minimizing the existing limitations. In this context, recognizing one's developmental situation is of key importance, identifying factors helpful in developing one's potential in particular. These factors undoubtedly include the resources at the disposal of people suffering from low vision. Research Aim: The aim of the research is to diagnose the psychosocial resources of people with low vision. Method: The study involved 110 low vision people and 110 sighted people at the age of 18-83, selected in terms of sex, age and education. The tools used in the research measured: basic hope, self-esteem and social support. Relevant calculations were made using the Student t-test for independent data. Results: The research showed that the low vision participants are characterized by a significantly lower intensity of basic hope. Moreover, they assess considerably less positively the properties that make up the family self and indicate that they receive significantly lower social support, both general and emotional as well as affirmative and practical. Conclusions: The obtained results indicate the necessity to undertake various actions aimed at improving the psychosocial functioning of people with low vision by optimizing their resources.